The impact of sport-based extracurricular activities on student engagement and academic achievement among Vietnamese students - Thi Ha Lan, Nguyen; Tuyet Mai, Le; Thi Thoan, Duong; Thi Cuc, Cao; Thi Thu Hoa, Pham; Thi Thanh, Nguyen (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study investigated the impact of sport-based extracurricular activities on student engagement and academic achievement among Vietnamese university students, addressing a gap in localized research. Employing a mixed-methods design, data were collected from 300 students and 60 faculty members across four universities. Quantitative data, derived from a student engagement questionnaire, grade point average (GPA) records, and participation surveys, were analyzed using descriptive statistics, correlation, and multiple regression analyses. Qualitative data from semi-structured interviews with 20 students and 10 faculty members were analyzed thematically. Results revealed a significant positive correlation between sports participation and engagement (r = 0.62, p < 0.01) and a moderate correlation with academic achievement (r = 0.35, p < 0.05), with engagement and sports participation explaining 32% of the variance in GPA (R² = 0.32). Qualitative findings highlighted enhanced motivation, social connectedness, and institutional barriers, such as limited facilities, as key factors. These results align with motivation theories, emphasizing the role of sports in fulfilling students’ needs for competence and relatedness. The study underscores the potential of sport-based extracurricular activities to enhance student outcomes in Vietnamese higher education, while highlighting the need for improved institutional support to overcome barriers.